2022
DOI: 10.3389/fimmu.2022.924734
|View full text |Cite
|
Sign up to set email alerts
|

Divergent complement system activation in two clinically distinct murine models of multiple sclerosis

Abstract: Multiple sclerosis (MS) is a neurological disease featuring neuroinflammation and neurodegeneration in young adults. So far, most research has focused on the peripheral immune system, which appears to be the driver of acute relapses. Concurrently, the mechanisms underlying neurodegeneration in the progressive forms of the disease remain unclear. The complement system, a molecular component of the innate immunity, has been recently implicated in several neurological disorders, including MS. However, it is still… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 57 publications
(82 reference statements)
1
7
0
Order By: Relevance
“…In this context, the viral infection animal models of MS, such as the TMEV and MHV-induced demyelination models, serve as a perfect template to explore the role of viruses in the pathogenesis of this condition and the importance of complement system activation ( Friedmann and Lorch, 1985 ; Katz-Levy et al, 1999 ; Mecha et al, 2013 ; Gilli et al, 2016a , b ). In line with this, using the TMEV model, Linzey et al (2022) found an increased expression of both classical and alternative complement pathway components. However, only the classical complement pathway activation as assessed by the level of C1q, C3, and C3aR1 expression, correlated with worse disease outcomes.…”
Section: Understanding the Role Of Early Complement Components And It...supporting
confidence: 69%
“…In this context, the viral infection animal models of MS, such as the TMEV and MHV-induced demyelination models, serve as a perfect template to explore the role of viruses in the pathogenesis of this condition and the importance of complement system activation ( Friedmann and Lorch, 1985 ; Katz-Levy et al, 1999 ; Mecha et al, 2013 ; Gilli et al, 2016a , b ). In line with this, using the TMEV model, Linzey et al (2022) found an increased expression of both classical and alternative complement pathway components. However, only the classical complement pathway activation as assessed by the level of C1q, C3, and C3aR1 expression, correlated with worse disease outcomes.…”
Section: Understanding the Role Of Early Complement Components And It...supporting
confidence: 69%
“…In TMEV-IDD, activation of the CS is evident at the early and chronic stages of the disease ( Libbey et al, 2010 ; DiSano et al, 2019a ; Linzey et al, 2022 ). In a recent study, the CS, specifically the classical complement pathway, was associated with TMEV-IDD pathogenesis, as the expression of critical complement components like C1q, C3, and C3aR1 were all correlated to a worse disease outcome ( Linzey et al, 2022 ).…”
Section: Neuro-immune Response In Theiler’s Murine Encephalomyelitis ...mentioning
confidence: 99%
“…In TMEV-IDD, activation of the CS is evident at the early and chronic stages of the disease ( Libbey et al, 2010 ; DiSano et al, 2019a ; Linzey et al, 2022 ). In a recent study, the CS, specifically the classical complement pathway, was associated with TMEV-IDD pathogenesis, as the expression of critical complement components like C1q, C3, and C3aR1 were all correlated to a worse disease outcome ( Linzey et al, 2022 ). In line with this finding, C1q and C3 depositions were observed in CNS regions characterized by inflammation, i.e., microglia and astrocytes activation, demyelination, and axonal damage ( Linzey et al, 2022 ).…”
Section: Neuro-immune Response In Theiler’s Murine Encephalomyelitis ...mentioning
confidence: 99%
See 2 more Smart Citations